Emerging risks of non‐native species escapes from aquaculture: Call for policy improvements in China and other developing countries - Rui‐Ting Ju; Xiao Li; Jia‐Jia Jiang; Jihua Wu; Jianguo Liu; Donald R. Strong; Bo Li (Wiley Online Library, 2025)
1. Global aquaculture relies heavily on the farming of non‐native aquatic species (hereafter, NAS). NAS escapes from aquaculture facilities can result in serious aquatic bio‐invasions, which has been an important issue in the FAO Blue Growth Initiative. A regulatory quagmire regarding NAS farming and escapes, however, exists in most developing countries. 2. We discuss aquaculture expansion and NAS escapes, illustrate emerging risks and propose recommendations for improved aquaculture management across developing countries and particularly for China. 3. In China, 68 NAS are known to have successfully established feral populations in natural habitats due to recurrent leakages or escapes; among the 68 NAS, 52 represent risks to native aquatic ecosystems. In addition to affecting a country's own biodiversity and ecosystem functions, NAS escapees can also threaten the biosecurity of shared waters in neighbouring countries. 4. Policy implications. Non‐native aquatic species (NAS) escapes have already had adverse ecological effects in China and other developing countries. The importance of this problem, however, is not adequately recognized by current conservation policies in developing countries. To conserve biodiversity and to support the goal of FAO's sustainable aquaculture, developing countries should now take responsible actions to address NAS escapes through policy and management improvements. Specifically, these countries should pass comprehensive legislation, establish effective agencies and national standards and planning and enhance integrated research and education to deal with risk assessment, prevention, monitoring and control of NAS escapes. Given that China is the world's largest aquacultural producer, China can create a model for other developing countries that will increase the biosecurity and sustainability of global aquaculture.